Knowledge about knee osteoarthritis among older adults: a qualitative study - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Tan, Maw Pin; Kumar, Saravana (2018)
Knee osteoarthritis (KOA) is associated with ageing. 40% adults with KOA reported the management to be ineffective. Self-management has been recommended as one of the components for successful management of KOA. Knowledge about KOA is important to empower older adults for self-management. However, there is limited information regarding knowledge of KOA among older population. The aim of our study was to explore knowledge on KOA among older adults with KOA. Three FGDs were conducted. Three male and Thirteen female older adults with KOA involved in the FGDs. Four main themes emerged regarding knowledge about KOA. Knowledge about KOA varies between individuals, ranging from no knowledge to sufficient knowledge about KOA development, KOA consequences, and KOA management. Even though participants had been living with KOA for many years, there is a demand for further information about KOA.